Macroeconomic Digital Book Development: How are the Feasibility of Experts and Student Responses? - Muslim, Fachruddiansyah; Refnida, Refnida; Chen, Diki; Wirayuda, Ricky Purnama (Universitas Pendidikan Ganesha, 2021)
There are still many teachers who have not used technology as a learning resource for students. This causes the teaching materials that students have less attractive. This study aims to see the product's feasibility, namely a digital book on macroeconomic material. The feasibility of the digital-book is divided into two, namely, the feasibility of the experts and the feasibility of the sample (students). This research is an R&D type with the selected development model, namely the ADDIE development model. The sampling technique used is simple random sampling with a sample of 36 active students of an economic education study program. There are 3 data collection instruments used, including media and material expert validation instruments with ten statements and student response instruments totalling 28 statements. Analysis of the data used in the form of descriptive statistics. The results of material validation for both validators were 42 (very good) and 37 (good), then for media experts, scores were 38 (good) and 39 (good), while for student responses to the material aspect, a score of 29.25 (recommended) was obtained. , the media aspect is 52.5 (highly recommended), the output aspect is 9.75 (recommended), and for all aspects, 91.5 (highly recommended). Based on the results obtained from the validation and small group trials, digital books on macroeconomic material are appropriate to be used as complementary learning resources in macroeconomics lectures.